Coastal Ecosystem Services Modeling in Latin America to Guide Conservation and Restoration Strategies: The Case of Mangroves in Guatemala and El Salvador - Hernández-Blanco, Marcello; Moritsch, Monica; Manrow, Marilyn; Raes, Leander (Frontiers in Ecology and Evolution, 2022)
We modelled the coastal protection and blue carbon ecosystem services provided by the mangroves of the Paz River Basin (El Salvador and Guatemala) using InVEST Coastal Vulnerability and Coastal Blue Carbon Models, with the goal of supporting the Regional Coastal Biodiversity Project of the International Union for the Conservation of Nature, in determining priority mangrove areas for conservation and restoration. To quantify the relative coastal protection that mangroves provide, we combined maps of different aspects of vulnerability, including ecological, physical, and social data. We also estimated carbon stocks, net sequestration, and the economic value of carbon sequestration as a service in 2050 and 2100. We then developed a combined index of coastal protection and carbon sequestration services to highlight priority conservation areas for mangroves. We found that in Guatemala the coastal protection service was provided in greater quantity in the province of Moyuta, while in El Salvador this service was the highest in the provinces of San Francisco Menéndez, Jujutla and Acajutla, which also had the greatest total carbon stock. In the Paz River basin, we estimate there are approximately 1,741 hectares of mangroves that provide the highest coastal protection and carbon sequestration services. Furthermore, we identified 318.9 hectares across both countries where mangroves could potentially be restored.